Beta‐propeller protein‐associated neurodegeneration: a case report and review of the literature - Stige, Kjersti Eline (Clin Case Rep, 2018)
Beta‐propeller protein‐associated neurodegeneration (BPAN) is a rare disorder, which is increasingly recognized thanks to next‐generation sequencing. Due to a highly variable phenotype, patients may present to pediatrics, neurology, psychiatry, or internal medicine. It is therefore essential that physicians of different specialties are familiar with this severe and debilitating condition.